Visualizing Abstract Grammar: How Augmented Reality Shapes Student Technology Acceptance in Nahwu Instruction - Anisa Anisa; Maman Abdurahman; Asep Sopian (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2026)
Nahwu is often considered difficult because the structure of nahwu is too theoretical. As a result, students show a low willingness to learn. The integration of Augmented Reality (AR) through Assemblr Edu Web is considered capable of attracting students' attention and increase willingness to learn. So, the aim of this research is to analyze the effect of perceived usefulness (PU) and perceived ease of use (PEOU) of AR on students' willingness to learn. The quantitative explanatory method was utilized in this research with PLS-SEM analysis techniques. This research provides evidence that the construct of PU has a significant effect on willingness to learn with a t-statistic value of 6.406 and a p-value of 0.000. The construct of PEOU has a significant effect on willingness to learn with a t-statistic value of 7.596 and a p-value of 0.000. This implies that when AR is regarded as useful and easy of use, the more students' willingness to learn in nahwu learning increases.